Variables de Control en un modelo de desarrollo con autoorganización: análisis de políticas económicas con presupuesto equilibrado - London, Silvia (Estudios de Economía, 2016)
The decades of 1950 and 1960 were the heyday of the Theory of EconomicDevelopment. Later on, difficulties in modeling the complex features of the developmentprocess and the failure of the policies recommended on the basis ofthe theory lead to the virtual demise of this area of research. The 1990s broughtabout a change in this trend, particularly due to the introduction of new features into the analysis of development processes. So, the renewed interest in thenature of complementarities and externalities, together with the emphasis onnon-linear models as well as on the institutional features of economies, lead toa fresh insight into the older presentations of Development Economics. In thisline, this work presents a discussion about certain formal tools that we thinkwill become handy in the analysis of development phenomena. We present anon-linear model of development, on which we perform a causality analysis, inorder to identify variables that could be selected as candidates to the applicationof control. This could help in the design of political economies. In fact, inthe paper we present a specific example of a policy intended to induce a fastdevelopment while keeping a balanced budget. Since in our model the nonlinearitieslead to self-organization, analytical solutions are not available. Therefore,we run simulations to show the results of using different control variablesfor the development process. It becomes evident that the variables detected inour causality analysis perform better. We draw from this fact general conclusionsthat we think may apply to every branch of Development Theory.